2007
DOI: 10.1074/jbc.m605653200
|View full text |Cite
|
Sign up to set email alerts
|

Closing the Gate to the Active Site

Abstract: Fatty acid amide hydrolase (FAAH) is a dimeric, membranebound enzyme that degrades neuromodulatory fatty acid amides and esters and is expressed in mammalian brain and peripheral tissues. The cleavage of ≈30 amino acids from each subunit creates an FAAH variant that is soluble and homogeneous in detergent-containing buffers, opening the avenue to the in vitro mechanistic and structural studies. Here we have studied the stability of FAAH as a function of guanidinium hydrochloride concentration and of hydrostati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…4, upper panel). This process is regulated by a phenylalanine residue (Phe432) located at the boundary between the two cavities, which may act as a "dynamic paddle" [21,45].…”
Section: Enzymatic Mechanism Of Faahmentioning
confidence: 99%
“…4, upper panel). This process is regulated by a phenylalanine residue (Phe432) located at the boundary between the two cavities, which may act as a "dynamic paddle" [21,45].…”
Section: Enzymatic Mechanism Of Faahmentioning
confidence: 99%
“…The fluorescence spectrum of FAAH is very broad due to the presence of more than one emitting species [37]; however, increasing the concentration of POPC vesicles led to a relevant red-shift of the wavelength at the emission maximum (λ max from 343.5 to 346.0 nm; Figure 3). The fluorescence spectrum of FAAH is very broad due to the presence of more than one emitting species [37]; however, increasing the concentration of POPC vesicles led to a relevant red-shift of the wavelength at the emission maximum (λ max from 343.5 to 346.0 nm; Figure 3).…”
Section: Faah Structure Is Modulated By Membranesmentioning
confidence: 99%
“…The catalytically active transmembrane domain-lacking ( TM) mutant of rat FAAH [1] was expressed with a His 6 tag in E. coli BL21(DE3)pLysS competent cells (Merck) using the pTrcHisAFAAH-TM plasmid [2] as reported previously [3]. Briefly, rat TM-FAAH cDNA was digested with the EcoRI and XhoI restriction enzymes, in phase with the coding sequence for the tail of six histidines, and was inserted into the pTrcHisA plasmid following a standard procedure (Invitrogen Life Technologies).…”
Section: Faah Purification and Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…al. 9 studied the stability of FAAH as a function of guanidinium hydrochloride concentration and hydrostatic pressure and concluded that conformational changes mediated by inhibitor binding to the active site lead to tighter interaction between monomers and an increase in enzyme stability. This also resulted in a reduced ability of the protein to bind to membranes.…”
mentioning
confidence: 99%